2018
DOI: 10.1186/s12302-018-0131-7
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of glyphosate-based herbicides on disease resistance and health of crops: a review

Abstract: Based on experimental data from laboratory and field, numerous authors have raised concern that exposure to glyphosate-based herbicides (GBHs) may pre-dispose crops to damage by microbial pathogens. In this review, we distinguish and evaluate two principal pathways by which GBHs may affect the susceptibility of crops to disease: pathway 1—via disruptions to rhizosphere microbial ecology, and pathway 2—via restriction of nutrients to crops. We conclude that GBHs have the potential to undermine crop health in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 96 publications
1
41
0
1
Order By: Relevance
“…Recent research has provided strong evidence that glyphosate does not cause mineral deficits, increased plant disease, or yield losses in GR soybeans (Bøhn et al 2014;Kandel et al 2015;Duke et al 2018). Despite this, concerns are still brought up regarding the effects of glyphosate on GR crops (e.g., Martinez et al 2018;Mertens et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has provided strong evidence that glyphosate does not cause mineral deficits, increased plant disease, or yield losses in GR soybeans (Bøhn et al 2014;Kandel et al 2015;Duke et al 2018). Despite this, concerns are still brought up regarding the effects of glyphosate on GR crops (e.g., Martinez et al 2018;Mertens et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ecotoxicological and resistance-related consequences of the extended use of glyphosate (Schütte et al, 2017) or of the use of GT GM crops (Pandolfo et al, 2018) have been emphasized, along with effects non-target terrestrial plants as well (Cederlund, 2017). As for emerging plant resistance against glyphosate, glyphosate itself and glyphosate-based herbicides have been shown to affect the disease resistance and health of plants by undermining their innate physiological defenses in mechanisms related to the mode of action of glyphosate, even in crops engineered for glyphosate-tolerance, and by interferences with the local microbial ecology in the rhizosphere (Martinez et al, 2018). The evolution of resistance was shown to occur due to gene amplification (Chen et al, 2017;Dolatabadian et al, 2017;Fernandez-Escalada et al, 2017;Han et al, 2017;Jugulam and Gill, 2018).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…A review of all GR crops by Hammerschmidt [13] determined there is no conclusive evidence that glyphosate increases the susceptibility of GR crops to disease. Another review [14] challenges this conclusion. For example, several studies have observed that GR beets and soybean have increased susceptibility to pathogens when glyphosate is applied at recommended rates [1416].…”
Section: Introductionmentioning
confidence: 97%
“…Another review [14] challenges this conclusion. For example, several studies have observed that GR beets and soybean have increased susceptibility to pathogens when glyphosate is applied at recommended rates [1416]. One study found no effect of glyphosate on disease induction in GR beets until rates exceeded normal field application rates by one order of magnitude [17].…”
Section: Introductionmentioning
confidence: 97%